Henry C. Mackall, The Maryland Code. Compiled by Otho Scott, and Hiram M’Cullough, Commissioners; Adopted by the Legislature of Maryland, January Session, 1860: The Acts of that Session Being Therewith Incorporated: With an Index to Each Article and Section Page 903, Image 899 (Vol. 2, 1860) § 128 - (:unkn) unknown (General Publisher, 1860)
They may impose a fine of one dollar on any person who may discharge a gun or other firearms in the said town on any day except on days when the militia may be mustered or paraded therein, and the like fine upon all persons who may suffer their chimneys or any of them to flame out; or upon any person driving, training or riding any horse at an immoderate gait through the streets.
--
Keywords: DISCHARGE